2000
DOI: 10.1007/s004170050375
|View full text |Cite
|
Sign up to set email alerts
|

The additive intraocular pressure-lowering effect of latanoprost 0.005% daily once and pilocarpine 2% t.i.d. in patients with open-angle glaucoma or ocular hypertension

Abstract: From the data we conclude that the additivity of latanoprost 0.005% is at least as effective as pilocarpine 2% t.i.d. in reducing IOP when added to eyes currently on monotherapy with timolol 0.5% b.i.d. Latanoprost was better tolerated than pilocarpine 2% eye drops in this study. The increase in iris pigmentation requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
2
9
0
1
Order By: Relevance
“…130,176,177 Addition of latanoprost to pilocarpine therapy does not appear to diminish uveoscleral outflow 178,179 but is instead additive, 178,[180][181][182][183] contrary to thoughts that ciliary muscle contraction with cholinergics hinders uveoscleral outflow. 179 In subjects (n = 115) with uncontrolled IOP on β-blocker monotherapy, adjunctive latanoprost (23.5%) or brimonidine (22.8%) were comparable in%IOPR at peak effect at one month, but brimonidine was better tolerated than latanoprost.…”
Section: Adjunctive Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…130,176,177 Addition of latanoprost to pilocarpine therapy does not appear to diminish uveoscleral outflow 178,179 but is instead additive, 178,[180][181][182][183] contrary to thoughts that ciliary muscle contraction with cholinergics hinders uveoscleral outflow. 179 In subjects (n = 115) with uncontrolled IOP on β-blocker monotherapy, adjunctive latanoprost (23.5%) or brimonidine (22.8%) were comparable in%IOPR at peak effect at one month, but brimonidine was better tolerated than latanoprost.…”
Section: Adjunctive Therapymentioning
confidence: 99%
“…137 The mean 24-hour diurnal curve was 19.2 ± 2.6 mmHg for latanoprost alone vs 16.7 ± 2.1 mmHg for FCLT in another trial. 197 A meta-analysis of randomized clinical trials of 1 to 3 months' duration 198 documented greater pooled IOP change from baseline with concomitant latanoprost and timolol (−6.0 mmHg), 67,130,176 than FCLT (−3.0 mmHg), 137,142 concomitant dorzolamide and timolol (−4.1 mmHg at trough and −4.9 mmHg at peak), or FCDT (−3.8 mmHg at trough and −4.9 mmHg at peak). Omission of the evening timolol dose with FCLT possibly explains the large difference in IOP between fixed and concomitant use.…”
Section: Pga/timolol Fixed Combinationsmentioning
confidence: 99%
“…The additional IOP reduction after six months was 24% for latanoprost and 20% for pilocarpine (2%) when these agents were added once or three times daily, respectively, to the eyes of 242 patients not adequately controlled on monotherapy with timolol [77]. Of 148 patients, also inadequately controlled with timolol alone each received additional treatment with either latanoprost once daily or pilocarpine three times daily, or their therapy was switched to latanoprost alone [76].…”
Section: β-Adrenergic Receptor Antagonistsmentioning
confidence: 99%
“…A combination of several drugs, including prostaglandin analogues, b-blockers, cholinergic agonists, adrenergic agonists, a 2 -stimulants, a 1 -blockers, and carbonic anhydrase inhibitors, have been reported to be effective. [1][2][3][4][5][6] These studies were carried out at the time when additional drugs were first administered in patients already receiving 1 drug. Several investigators demonstrated that patients with less dosing showed better adherence and higher persistency.…”
Section: Introductionmentioning
confidence: 99%